Pengaruh Hospitable Teledentistry Terhadap Pengurangan Isolasi Dan Kecemasan Sosial Serta Meningkatkan Kepuasan (Fakultas Ekonomi Universitas Gresik, 2023)
Teledentistry is the concept of telemedicine equivalent in dental practice. Hospitality has been recognized in the hospital setting, but its role and implications for teledentistry are poorly understood. Analyzing the positive influence of humantechnology interaction and human-human interaction on patient satisfaction, reduction of isolation and reduction of anxiety with competency mediating variables and perceptions of patient control. Analysis of research variables was carried out using Partial Least Square (LPS). Analysis of the influence between variables, both directly and indirectly, was carried out using Structural Equation Marketing (SEM). Data was collected from 300 respondents who used teledentistry. Human-technology interaction has a significant effect on patient's perceived competence and control. Human human interaction has a significant effect on the patient's perceived competence and control. Perceived control can mediate human-to-human interaction and technology to patient satisfaction. Whereas competence only mediates humanto-human interactions on patient satisfaction. Perception of control can mediate human-to-human interactions and technology to reduce isolation. Meanwhile, competence only mediates human-to-human interactions in reducing isolation. Perceived control can mediate human-to-human interactions and technology to reduce anxiety. Meanwhile, competence can only mediate human-to-human interactions in reducing anxiety. This research is used as an evaluation material for managerial teledentistry in maintaining and increasing patient satisfaction and reducing isolation and anxiety